ChemInform Abstract: Organic Stereochemistry. Part 4. Isomerisms about Single Bonds and in Cyclic Systems. Issue 28 (21st June 2013) - Testa, Bernard; Vistoli, Giulio; Pedretti, Alessandro
Abstract Review: ca. 150 refs.